UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI KERJA DAN KOMPETENSI PROFESIONAL GURU PENDIDIKAN AGAMA ISLAM - Shoim (UNISAN JURNAL, 2024)
: This examination intends to depict and dissect the impressive skill and execution of PAI SDIT and SMPIT Insan Harapan Batam instructors as well as the endeavors made to further develop understudy learning accomplishment. This examination is a subjective field study and uses a clear scientific methodology. Information assortment was completed utilizing perception, meetings and documentation strategies. Information examination is completed by giving importance to the information gathered and afterward making inferences. The consequences of the exploration show a connection between the initiative style of the madrasa head and the instructive qualities of SDIT and SMPIT Insan Harapan Batam understudies with an importance t of 0.002 < 0.05. This implies that the initiative style of the madrasa head impacts the instructive qualities of understudies at SDIT and SMPIT Insan Harapan Batam with a level of 67.5%; 2) The connection between instructor execution and understudy instructive attributes at SDIT and SMPIT Insan Harapan Batam with an importance t of 0.000 < 0.05. Subsequently, educator execution emphatically affects understudy learning accomplishment at SDIT and SMPIT Insan Harapan Batam with a level of 69.9%; 3) The connection between the initiative style of the madrasa head and instructor execution on instructive qualities at SDIT and SMPIT Insan Harapan Batam with an importance F of 0.002 < 0.05 with a level of 70.3%. By taking a gander at the consequences of the meaning of F in the Anova test did, it is realized that the F esteem is 0.002, it is realized that the initiative style of the madrasa head impacts endeavors to work on the exhibition of educators and understudies. learning accomplishment. The better the nature of the madrasa head's initiative style on educator execution at SDIT and SMPIT Insan Harapan Batam, the better the understudy learning accomplishment at SDIT and SMPIT Insan Harapan Batam.